Traumatic brain injury reprograms lipid droplet metabolism shaped by aging and diet in Drosophila brain - Stacey A. Rimkus; Barry Ganetzky; David A. Wassarman (PLoS ONE, 2025)
Traumatic brain injury (TBI) initiates secondary cellular damage such as mitochondrial dysfunction, oxidative stress, and neuroinflammation. In neurodegenerative disorders, these stressors are associated with accumulation of lipid droplets (LDs) – organelles that store neutral lipids to provide energy and protect cells from lipid toxicity. However, the regulation of LD metabolism following TBI remains poorly understood. Using a Drosophila melanogaster model, we investigated how TBI influences LD accumulation, particularly in relation to aging and diet, other LD modulatory factors. Confocal microscopy of fly brains at one day after injury showed increases in both LD size and number. The rise in LD number occurred only in flies fed a carbohydrate-rich diet and was absent in those given a ketogenic diet (KD) or water, suggesting that glucose availability is necessary for LD formation post-injury and potentially underlying why KD and water do not elicit the deleterious outcomes observed with carbohydrates. Lipidomic analysis of fly heads further revealed elevated levels of triacylglycerol (TG) species typically stored in LDs, indicating enhanced lipid synthesis post-injury. By seven days post-injury, LD size and number returned to baseline levels observed in uninjured flies and remained stable through 14 days post-injury. However, by 21 days post-injury, uninjured flies showed a marked increase in LD number that was not observed in injured flies, although LD size increased in both groups. These findings suggest that TBI selectively impairs age-dependent production of new LDs without affecting the growth of existing LDs. Importantly, TG levels remained elevated in heads of injured flies, indicating that the reduction in LD number was not due to limited lipid availability. Together, our findings indicate that TBI acutely induces LD formation as a protective response but chronically impairs LD biogenesis, disrupting lipid homeostasis in an age- and diet-dependent manner that may contribute to neurodegeneration.